Individualized Tacrolimus Therapy for Pediatric Nephrotic Syndrome: Considerations for Ontogeny and Pharmacogenetics of CYP3A - Sun, Jie-Yu; Xu, Ze-Jun; Sun, Fang; Guo, Hui-Lei; Ding, Xuan-Sheng; Chen, Feng; Xu, Jing (Current pharmaceutical design, 2018)
Tacrolimus is used initially as an immunosuppressant drug in solid organ transplant population. This calcineurin inhibitor has also been recommended by KDIGO Clinical Practice Guideline for Glomerulonephritis for the treatment of nephrotic syndrome in children and adults. Tacrolimus is characterized by a narrow therapeutic index and large pharmacokinetic (PK) variations. Therefore, routine Therapeutic Drug Monitoring (TDM) is critical to keep tacrolimus blood levels within the therapeutic range. Tacrolimus is mainly metabolized by cytochrome P450 (CYP) enzymes 3A5 and 3A4. Actually, for pediatric patients, they are totally different to adults. Profound changes in CYP3A expression and activity occur throughout fetal life and in the neonatal and childhood periods thereby influencing their catalytic function. CYP3A7, CYP3A5, and CYP3A4 display an age-dependent maturation pattern. Notably, the CYP3A7-CYP3A4 switch taking place during the very early life will affect tacrolimus metabolism. Meanwhile, CYP3A isoforms are polymorphic enzymes, especially for CYP3A5. The guideline has recommended that the tacrolimus dosage should be adjusted according to the CYP3A5 genotype. Additionally, genetic CYP3A4 variation (e.g., CYP3A4*22) is also associated with interindividual variability of exposure level to tacrolimus. However, age (ontogeny) sometimes trumps genetics (genotype) in determining the enzymatic functions (phenotype) in pediatric patients. It's important to discriminate at what age the ontogeny plays key roles and at what age genetic variation become a major determinant. Thus, we need to better understand the mechanisms driving the CYP3A maturation and integrate ontogeny and genetics into the tacrolimus disposition, thereby tailoring the dosage individually for pediatric NS patients at different developmental stages.